Produtividade de alho-porró via fertirrigação nitrogenada - Souza, Alice Rodrigues de (2018)
The objective of this study was to verify the nitrogen (N) doses effect in leek cultivar productivity applied through fertirrigation. We realized this project at Faculdade de Ciências Agrárias of Universidade Federal da Grande Dourados, where the soil is Dystroferric Red Latosol. We realized this experiment between April and September of 2017. This experience studied four doses of N (0, 100, 200 and 300), which were applied 15, 30 and 45 days after the transplanting (DAT) of seedlings through fertirrigation. Randomized blocks, with 8 repetitions, were the experimental design used. ‘Carentan’ (Feltrin®) was the cultivar used. The transplant occurred 61 days after the seeding (DAS) and the harvest, 103 DAT. We analyzed the following variables: Commercial and total productivity. We subjected the data to analysis of variance (p≤0,05), and to regression analysis to verify the effect of nitrogen on the evaluated characteristics. The nitrogen application shows itself as positive to leek productivity, however the tested dosed did not attain the greatest productivity, but, through regression analysis models, we estimated the best results with 382 and 372 kg ha-1 of N to commercial productivity and 343 and 361 kg ha-1 of N to total productivity.